Belgica-7904: A new carbonaceous chondrite from Antarctica; Minorelement chemistry of olivine - Skirius,C.; Steele,I.M.; Smith,J.V. (1986)
P(論文) Belgica-7904 is an unusual C2 meteorite which lacks pyroxene. It contains two groups of clasts, and three types of olivine distinguished by red, blue or no cathodoluminescence. Seven clasts in the first group are characterized by red forsterite ((Fo)_<99-98>) in a cryptocrystalline greenish-brown matrix. The red forsterite is subhedral, equigranular, and contains numerous brown and Ni-Fe inclusions. One of these clasts contains inclusion-free blue forsterite grains with red margins. These seven clasts are encircled by an opaque rim. Two clasts of the second group have no opaque rim, and consist of blocky to euhedral Fe-rich olivine (first (Fo)_<83-67>; second (Fo)_<56-41>) which lack luminescence. The second of these clasts contains a small grain of blue forsterite rimmed by Fe-rich olivine. The forsterites show unusually high levels of the refractory elements Al, Ca and Ti with positive intercorrelations; blue ones have higher concentrations than most red ones. Manganese, Cr and Fe show strong positive correlations with lower concentrations in the blue olivines; they are negatively correlated with Al, Ca and Ti. The Fe-rich olivines of the second clast group have lower levels of Ca, Ti and Al. It is proposed tentatively that the inclusion-free blue forsterites may be relic grains formed by condensation from a vapor rich in refractory elements, and that the inclusion-bearing red forsterite and the non-luminescent Fe-rich olivines formed from separate liquids. Pyroxene is absent from both the clasts and separate mineral grains. The minor-element chemistry of the forsterites in B-7904 is different from that for Allende (CV3), and is similar to that for one group of forsterites in Murchison (C2). It is certain that the olivines in B-7904 require a complex history probably involving initial condensation from a refractoryrich vapor, partial melting and reaction with other materials, and crystallization from more than one type of melt. The minor-element chemistry and textures of olivines in ...